Desain Kelembagaan Usaha Hutan Rakyat untuk Mewujudkan Kelestarian Hutan dan Kelestarian Usaha dalam Upaya Pengentasan Kemiskinan Masyarakat Pedesaan - . Hardjanto; Yulius Hero; Soni Trison (Jurnal Ilmu Pertanian Indonesia, 2012)
People forests in Java, have been around since 1950s, and it has been sustaining naturally following the market without any intervention. Nowadays, it keeps developing, with the increase in market demand and wood processing industry. People forest system consists of four sub-systems, those are: production, processing, marketing, and institutional sub-systems, which are simultaneously and dynamically interrelated in a system. The institutional sub-system requires collaborative arrangement that involves many parties. The objectives of the study were: 1) to identify knowledge, actors/networks, and interest/dynamic of people forest, 2) to analyze policy space of people forest management, and 3) to make a design of a people forest institution. The results showed that 1) The knowledge in people forest business came from families, neighbors, and government programs, 2) Actors of people forest agribusiness consisted of primary and secondary actors, 3) Cooperative relationship among actors of people forest business was mainly in the interest of gaining profit for each party,and 4) Institutional designs aimed at solving problems in policy space of people forest management.